Role of Cytosorb in Severe Covid 19 Patients to Combat Cytokine Storm - A Case Series of 3 Patients (Global Journal of Medical Research, 2022)
PURPOSE: To demonstrate the effect of Cytosorb on reducing the cytokine levels seen due to cytokine storm in severe COVID 19 patients. MATERIAL
Keywords: COVID-19 disease; cytosorb therapy; 9-point ordinary scale developed by WHO